PROSPECTS FOR THE DEVELOPMENT OF PRODUCERS IN THE MARKET OF FRUITS AND BERRIES OF UKRAINE - KRYKAVSKYY, JEVHEN; KUZO, NATALIIA; KOSAR, NATALIIA; CHERKES, ROMAN (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The conducted study of the fruit and berries market of Ukraine shows significant opportunities for the further development of their producers both in the domestic and foreign markets. This is because the demand for them is growing and Ukraine is characterized by favorable location and favorable natural and climatic conditions. The development of this market is negatively affected by the short shelf life of fruits and berries in fresh form, as a result of which a significant part of them are exported in processed and frozen form. Ukrainian enterprises have significant opportunities for the supply of berries in the form of dried products, taking into account the existing EU standards for these products, the prices of which on the world market are quite high. To ensure the proper quality of fresh fruits and berries, their proper storage and transportation should be organized, the functioning of the "cold" chain in the form of "manufacturer - transport - warehouses - transport - the final retail network of trade." Organic berries today are a fashionable and sought-after niche product. Ukrainian manufacturers have great opportunities to supply these products to the foreign market. The data of secondary marketing information indicates that Ukraine ranks 11th among all European countries in terms of the total area of land that is certified as organic. Organic land accounts for less than 1% of all agricultural land in Ukraine, which determines Ukraine's significant potential in this area. However, the entry of domestic producers into the world market of fruits and berries requires obtaining certificates under international standards, which requires additional funds and efforts from them. The built trend models show that raspberry and blackberry and gouge berry crops are promising for cultivation by farms and the population in Ukraine. Due to the existing climatic conditions, berry crops can be grown throughout Ukraine. Most of them are grown and harvested in such regions as Zhytomyr, Kyiv, and Donetsk. New opportunities under quarantine restrictions for domestic producers of fruits and berries to find new consumers and markets opens online promotion (through participation in world exhibitions, website development in several languages, social media presence, etc.) and online sales.
Keywords: market of fruits and berries of Ukraine; volumes of production of fruits and berries; import of fruits and berries; export of fruits and berries; organic berries